Comparison of velocity and percentage-based training on maximal strength: meta-analysis - Zhang, M.; Tan, Q.; Sun, J.; Ding, S.; Yang, Q.; Zhang, Z.; Lu, J.; Liang, X.; Li, D. (International Journal of Sports Medicine, 2022)
The purpose was to analyze the comparison of velocity-based resistance training and one-repetition maximum (%1RM) percentage-based training in maximal strength improvement by meta-analyzing and to find the reasons for the controversial findings of different studies. Ten studies were included in the systematic review and seven were subjected to meta-analysis. A total of 139 subjects were selected from the included articles after exclusion, including athletes of different specialties (N=93) and non-athletes mainly from fitness groups (N=46). The overall effect size was SMD=0.26 (95%CL 0.03 to 0.49, P=0.03, I²=0). As for the comparison of the analysis of different intervention objects as subgroups, the effect size of athletes as the subgroup was 0.35 (95%CI 0.06 to 0.64, p=0.02, I²=0), indicating that in the RCT with athletes as the intervention target, the effect of VBRT in improving the maximal strength was significantly different from that of PBT. Velocity-based resistance training might be more effective than percentage-based training in maximal strength improvement, in which velocity-based resistance training is more suitable for athletes in season, while percentage-based training is more suitable for the general sports population. More high-quality researches should deal with the effect of other athletic performance with velocity-based resistance training in the future.